History of international broadcasting. Volume 2. - Wood, James 1920- (London, United Kingdom Institution of Engineering and Technology, 2000)
The book reviews developments in the following fields: international broadcasting; short-wave (SW) sales; foreign policy; broadcast transmitter industry; antenna arrays; and tube manufacturing industry.
Vol. 2 published by the Institution of Electrical Engineers in association with the Science Museum.
Electronic reproduction.
Keywords: International broadcasting; Electronic books